2016
DOI: 10.1096/fj.201600393r
|View full text |Cite
|
Sign up to set email alerts
|

JNK1 ablation in mice confers long‐term metabolic protection from diet‐induced obesity at the cost of moderate skin oxidative damage

Abstract: Obesity and insulin resistance are associated with oxidative stress, which may be implicated in the progression of obesity-related diseases. The kinase JNK1 has emerged as a promising drug target for the treatment of obesity and type 2 diabetes. JNK1 is also a key mediator of the oxidative stress response, which can promote cell death or survival, depending on the magnitude and context of its activation. In this article, we describe a study in which the long-term effects of JNK1 inactivation on glucose homeost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…However, melittin, the main constituent of apitoxin, improves insulin sensitivity through the activation of phospholipase A2 in diabetic mice induced by diet [ 56 ]. Both apitoxin and melittin may have contributed to the glycemic control observed in this study, although insulin resistance is the predominant mechanism that triggers diet-induced diabetes [ 57 , 58 , 59 ], which was the model used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…However, melittin, the main constituent of apitoxin, improves insulin sensitivity through the activation of phospholipase A2 in diabetic mice induced by diet [ 56 ]. Both apitoxin and melittin may have contributed to the glycemic control observed in this study, although insulin resistance is the predominant mechanism that triggers diet-induced diabetes [ 57 , 58 , 59 ], which was the model used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…To learn about the long-term effects of JNK1 ablation in mammals undergoing metabolic stress from obesity, we have investigated mice lacking JNK1 (JNK1 −/− ) that are chronically fed an obesogenic high-fat diet for the duration of their lifetime [82] . The results showed that, compared to control mice, JNK1 −/− mice maintained on high-fat diet display normal life-span and long-term sustained protection from obesity, hepatic lipid accumulation, adipose tissue inflammation, and insulin resistance.…”
Section: Role Of Jnk In the Cell Response To Metabolic Stress: Emergimentioning
confidence: 99%
“…Measurement of lipid peroxidation in different tissues showed that oxidative damage in JNK1 −/− mice fed a high-fat diet for 40 weeks was similar-to-controls in kidney and heart, slightly improved in the liver and largely improved in adipose tissue, but was significantly worsened in the skin. The protective effects of JNK1 ablation on liver and fat oxidative stress were proposed to be, at least in part, a consequence of the reduced steatosis and reduced adipose tissue inflammation, whereas increased skin oxidative damage was correlated with a local reduction of the expression of antioxidant genes [82] .…”
Section: Role Of Jnk In the Cell Response To Metabolic Stress: Emergimentioning
confidence: 99%
“…39 Total RNA quality and quantity was evaluated on a denaturing agarose gel. RNA was retro-transcribed using a commercial kit (Promega), and cDNA used to perform real-time quantitative PCR using a commercial SYBR-Green mix (Biorad) and specific primer sequences 11,40,41 listed in Table S1. For immunostaining, after fixation in 4% buffered formaldehyde, liver and fat tissues were embedded in paraffin, and cut into 5 µm thick sections.…”
Section: Molecular and Histopathological Analysis Of Liver And Adipmentioning
confidence: 99%
“…2 Because of the importance of the context in determining the outcome of JNK signaling in stress response, it is necessary to evaluate the effects of JNK inactivation on different stages of the progression of obesity-driven diabetes. However, while the role of different JNK isoforms in obesity-driven insulin resistance has been extensively investigated, 6,7,[9][10][11][12][13][14][15][16][17][18][19][20] the effects of JNK ablation on obesity-driven loss of functional pancreatic β-cells was not investigated to the same extent.…”
Section: Introductionmentioning
confidence: 99%